Perancangan Perancangan Sistem Trasmisi Mesin Pres Hidrolik Kapasitas 3 Ton Dengan Penggerak Motor listrik - Prayuda, Gilang Angga; Prihastuty, Endang; Tohasan , Achmad (Universitas Majalengka, 2024)
Technological advances have encouraged improvements in the industrial sector in developing countries, including Indonesia. This is of course supported by several factors, including the use of modern equipment as a substitute for human labor. It can be said here that the more modern an industry is, the more machine power is used while the less human power is needed. As human needs become increasingly greater, the machine industry is currently also developing very rapidly. Developments in the industrial sector are marked by the creation of various types of machines that can assist human activities. The use of machines can help human activities or work to be more efficient in terms of completion time, as well as reducing the risk of work accidents. Currently, machines are used as tools that have high automation and precision. Therefore, many people use machines for everything, one of which is a pressing machine. A pressing machine is a tool made to compress or press an object, the power source can come from hydraulics, human power, electric motors and others. The aim of this final project is to design a transmission system for a 3 Ton Semi-Automatic Hydraulic Press Machine with an electric motor drive. It can increase the author's knowledge, insight and experience regarding planning a machine. Conclusion Ball bearings with type 6203 require an installation time of 1 minute 35 seconds and removal of 1 minute 32 seconds. Ball bearings of type 6305 receive a pressure of 400 psi to be installed on the shaft, and when released the pressure produced is the same, namely 400 psi to be able to leave the shaft. A type 6206 ball bearing with a shaft length of 77 mm takes 3 minutes 32 seconds to install, while the same shaft length takes 3 minutes 22 seconds to remove from the shaft.